ANTI-STRESS ACTIVITY OF DIFFERENT COMPOSITIONS OF PANCHAGAVYA AND ALOE BARBEDANSIS MILL BY USING TAIL SUSPENSION METHOD. Issue 4 (2013) - Kumar, Amit; Kumar, Rahul; Kumar, Kuldip; Gupta, Vaishnavee; Shrivas, Triveni; Tripathi, Kishu
No abstract available